In vitro, antioxidant activity and cream formulation of alkaloid extracts Perna viridis. (May 2019) - Franyoto, Y D; Kusmita, L; Mutmainah; Pertiwi, Y P
Abstract: Photoaging is a common problem that occurs in our community due to ongoing exposure to ultraviolet rays. The use of antioxidants is an effective approach to prevent symptoms related to photo-induced aging of the skin. The objective of this study was to purification alkaloid and to formulate antioxidant cream extract Perna viridis. Thus, the present study was to prepare and evaluate the antioxidant cream extracts of Perna viridis for their radical scavenging activity. Perna viridis is one of the economically important biotas. This biota is diverse in Indonesia waters and occurred in coastal, mangrove area and estuarine. Initially, the material was macerated gradually with ethanol. The extract obtained was filtered and evaporated. The extracts were fractionated and analyzed by Thin-layer Chromatography. The extracts were examined for DPPH (2, 2 - diphenyl - 1- picrylhydrazyl) radical scavenging activity with reference standard ascorbic acid through in vitro models. The ethanolic extract Perna viridis was found to act in scavenging DPPH radicals with ascorbic acid used as the reference standard, and an IC50 value was found to be 90.17 μg/mL. The results showed that these extracts of Perna viridis could be considered as natural antioxidants and may be useful for curing diseases arising from oxidative deterioration.